House arrest - Ionescu, Larisa Cristina (Eximia, 2023)
The right to physical freedom is one of the most obvious rights and freedoms, being the subject of the Constitution, as a fundamental law, as well as of numerous treaties, conventions and other such acts to which our country is a party. Man, by nature, is individual. This character of man has made him over time to fight continuously with the tendency to freedom. We can affirm that the feeling of freedom was born and ascended with man, therefore for the human being it has been and will remain as natural and legitimate as existence itself. However, the association of man in a social grouping, in the sense of the state, compels him to observe the norms to which the state is subject. Living in society, man must accept, in order to achieve the general interest, the "common social good", the limitation of his forms of manifestation to the dimensions of the reasonable. This can be done, which is preferable, through self-control, but this is an uncertain, variable, random path. More certain is the intervention of an external factor, constituted in society by the coercive force with which public power is endowed. It is a path that has the advantage of permanence, proportionality, the possibility of being controlled. Institutionalized coercion is not only an exclusive dimension of public power, but it is also its essential dimension. Of course, as a method of governing state power, persuasion takes precedence, coercion having a subsidiary role, but it is ubiquitous. Any state-organized society has a coercive force, varying only the forms of realization of coercion, its intensity, and the relations between coercion and persuasion. The measure of house arrest can be considered easier compared to other preventive measures of criminal proceedings, which, by definition, represent the deprivation of liberty of a person during criminal proceedings in order to ensure its proper conduct.